Integrating Research-Supported Coaching Practices Into Secondary Teachers’ Team Meetings: Early Indications of Potential to Impact Collaborations, Classroom Interactions, and Student Engagement - Stuhlman, Megan; Mikami, Amori Yee; Hofkens, Tara; Allen, Joseph; Pianta, Robert; Smit, Sophie (Frontiers in Education, 2022)
The My Teaching Partner-Secondary (MTPS) program demonstrated improvements in classroom interactions and student outcomes in secondary schools using one-on-one coaching between study staff and teachers. Despite promising results, the time, cost, and oversight from a university research team may pose barriers to adoption of coaching programs like MTPS at scale. The My Teaching Team (MTT) project sought to translate key ingredients from MTPS into existing professional development contexts that are already built into many middle and high school educators’ weekly schedules: co-planning or professional learning community meetings. Six teams of secondary teachers (N = 30 teachers) participated in a pilot test of the usability of MTT materials across 5 months in one school year. Three teams elected to use MTT materials, and three elected to be a comparison group who continued their typical practices. Teams adopting MTT materials were observed to do so with good implementation integrity, and reported satisfaction with the intervention. Compared to typical practice teams, those using MTT were observed to spend more meeting time discussing teaching practice and less time discussing logistics/mechanics, and engaged in more video sharing and feedback to team members in the MTT sessions that explicitly encouraged this. The number of MTT meetings completed by a team, as well as spending more time discussing teaching practices and video sharing (but not feedback provided) during team meetings, predicted students’ self-reports of greater engagement and observations of higher levels of emotional support provided in the classroom. Implications for translating empirically-supported interventions from the lab to real-world school settings are discussed.